2014
DOI: 10.1016/j.biortech.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cloth stimulates direct interspecies electron transfer in syntrophic co-cultures

Abstract: h i g h l i g h t sConductive carbon cloth stimulated syntrophic metabolism in DIET co-cultures. Carbon cloth did not stimulate metabolism in a co-culture that relied on H 2 transfer. Non-conductive cotton cloth did not facilitate DIET. Carbon cloth restored DIET in Geobacter strains missing pili or OmcS cytochrome. a r t i c l e i n f o t r a c tThis study investigated the possibility that the electrical conductivity of carbon cloth accelerates direct interspecies electron transfer (DIET) in co-cultures. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(166 citation statements)
references
References 34 publications
3
158
0
5
Order By: Relevance
“…One way to increase the efficiency of DIET is to add conductive materials such as granular activated carbon (GAC), carbon cloth, graphite, biochar, magnetite (Fe 3 O 4 ) particles, etc., into methanogenic digesters [79][80][81][82]. When GAC was added, aggregation became weaker, but metabolism was substantially accelerated.…”
Section: Diet In Microbial Aggregatesmentioning
confidence: 99%
“…One way to increase the efficiency of DIET is to add conductive materials such as granular activated carbon (GAC), carbon cloth, graphite, biochar, magnetite (Fe 3 O 4 ) particles, etc., into methanogenic digesters [79][80][81][82]. When GAC was added, aggregation became weaker, but metabolism was substantially accelerated.…”
Section: Diet In Microbial Aggregatesmentioning
confidence: 99%
“…Chen et al [11] successfully confirmed the accelerating effect on DIET metabolism of carbon cloth addition in co-cultures of G. metallireducens with G. sulfurreducens or M. barkeri. The DIET metabolism between these species was not stimulated in co-cultures with poorly conductive cotton cloth, indicating that the electrically conductive characteristic of the carbon cloth is the major reason for the enhancement in metabolism.…”
Section: Carbon Fibersmentioning
confidence: 92%
“…However, DIET can also occur through conductive materials as nonbiological electric conduits, as shown in Figure 2C [11]. Under a conductive-materialsupplemented environment, microorganisms do not form tight aggregates of the kind that are necessary for direct physical contact or electrical connection through pili between cells; instead, they seem to be tightly attached to the surface of the conductive materials [11,12,14] (Figure 3). Furthermore, important biological tools for DIET, such as pili and cytochrome OmcS, are not required for electron exchange if conductive materials exist.…”
Section: Conductive Materials To Promote Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…was ruled out because the electrode was poised at a potential that was too high for appreciable hydrogen production [26]. Also G. metallireducens is not able to use hydrogen as an electron donor, and a strain of G. sulfurreducens in which a gene for the hydrogenase required for hydrogen uptake had been deleted reduced fumarate as well as wild-type cells [24,27,28].…”
Section: Electrons Exchangementioning
confidence: 99%